Aggregate formation in crystalline blends of α-sexithiophene and para-sexiphenyl. (31st August 2021) - Bhagat, Shubham; Leal, William D; Majewski, Marek B; Simbrunner, Josef; Hofer, Sebastian; Resel, Roland; Salzmann, Ingo
Abstract: Earlier reports on rod-like conjugated molecules of similar shape and size such as α-sexithiophene (6T) and para-sexiphenyl (6P) indicated mixed crystal growth in equimolar blends. The spectral overlap between the 6P fluorescence and 6T absorption might there give rise to resonant energy transfer between the two species. In marked contrast to H-type aggregation found for 6T bulk crystals, isolated monolayers of 6T as well as 6T monolayers sandwiched between 6P multilayers have been reported to show pronounced green (instead of red) fluorescence, which has been attributed to J-type aggregation. Here, we investigate whether these altered optical properties of 6T translate from the monolayer to a bulk equimolar blend with 6P. Insight into the mixed crystal structure for vacuum co-deposited films of 6T + 6P is provided by using synchrotron grazing-incidence x-ray diffraction on different substrates. By correlating the optical properties of the pure and the mixed systems using absorption and photoluminescence spectroscopy we identify the green emission known from 6T monolayers to prevail in the blend. Our analysis indicates the formation of aggregates which are promoted by the molecular arrangement in the mixed crystal structure highlighting that the remarkable optical properties of 6T/6P heterostacks translate into mixed crystalline films. This study underlines that tuning the opto-electronic properties of organic semiconductors by blending species of similar shape but distinct opto-electronic properties is a promising pathway to achieve altered material properties.